2016
DOI: 10.1039/c6nj01198e
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational spectrum of 1,4-dioxane in aqueous solution – theory and experiment

Abstract: Frequency shifts in dioxane–water mixtures were studied using conductor-like screening and explicit solvation models, showing predominance of the latter one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The CH 2 stretching vibrations of 1,4-dioxane adsorbed onto ZSM-5 in n -hexane, methanol, and aqueous solutions were at 2960.8, 2970.5, and 2976.1 cm –1 , respectively, which was reported to be 2968 cm –1 for 1,4-dioxane . This shows the presence of hydrogen bonds formed through CH 2 groups of 1,4-dioxane with water, which is consistent with similar findings reported in the literature . The significantly greater adsorption of 1,4-dioxane in aqueous solution than in methanol or hexane solutions (Figure S6A) suggests that these 1,4-dioxane–water complexes are adsorbed onto the zeolite.…”
Section: Resultssupporting
confidence: 90%
“…The CH 2 stretching vibrations of 1,4-dioxane adsorbed onto ZSM-5 in n -hexane, methanol, and aqueous solutions were at 2960.8, 2970.5, and 2976.1 cm –1 , respectively, which was reported to be 2968 cm –1 for 1,4-dioxane . This shows the presence of hydrogen bonds formed through CH 2 groups of 1,4-dioxane with water, which is consistent with similar findings reported in the literature . The significantly greater adsorption of 1,4-dioxane in aqueous solution than in methanol or hexane solutions (Figure S6A) suggests that these 1,4-dioxane–water complexes are adsorbed onto the zeolite.…”
Section: Resultssupporting
confidence: 90%
“…However, instead of simple residual solvent, they are believed to be generated from dioxane-polymer and dioxane-TU interactions, since these peaks show varying shifts or band shape changes from neat dioxane ( Table 1). [31][32][33][34] Similar to many other PMMA complex studies, [35][36][37][38] no significant shift is observed in the PMTD complex for the band of the PMMA acrylate carboxyl group located at 1727 cm −1 . However, the symmetric stretching vibrations of methylene groups at 2849 cm −1 in the spectrum of PS [39] shift to a larger wavenumber at 2859 cm −1 in the PSTD sample.…”
Section: Formation Of A-pmma-tu-14-dioxane Metastable Complex (Pmtd)supporting
confidence: 82%
“…However, instead of simple residual solvent, they are believed to be generated from dioxane–polymer and dioxane–TU interactions, since these peaks show varying shifts or band shape changes from neat dioxane ( Table 1 ). [ 31–34 ]…”
Section: Resultsmentioning
confidence: 99%
“…Contamination of poplar by THF appeared at 2977 and 2875 cm −1 for its C-H stretching, 1063 cm −1 for ring deformation, and 912 cm −1 for CH 2 twisting [39]. The bands of dioxane were observed at 2960, 2890, 1457, 1322, 1255, 1119, 1057, 889 and 872 cm −1 to show its equatorial (higher frequency) C-H stretching, axial (lower frequency) C-H stretching, symmetric CH 2 deformation, CH 2 wagging, CH 2 twisting, C-O-C symmetric stretching, ring trigonal deformation, C-C stretching, and C-O-C stretching, respectively [40]. The addition of toluene on poplar caused three bands including 3069 cm −1 for C-H stretching, 1497 cm −1 for C-C stretching, and 728 cm −1 for C-H out of plane bending [41].…”
Section: Commonly Used Pretreatment and Preprocessing Solventsmentioning
confidence: 99%
“…FTIR band assignments of common biomass processing solvents on poplar[32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Cont.…”
mentioning
confidence: 99%